Axonal and glial microstructural information obtained with diffusion-weighted magnetic resonance spectroscopy at 7T - Ronen, Itamar; Ercan, Ece; Webb, Andrew (Frontiers in Integrative Neuroscience, 2013)
Diffusion weighted magnetic resonance spectroscopy (DWS) of brain metabolites offers unique access to compartment-specific microstructural information on tissue, and to a more sensitive detection of compartment-specific changes in tissue in health and disease. The specificity of DWS is offset, however, by its relative low sensitivity, intrinsic to all MRS-based methods, and further exacerbated by the signal loss due to the diffusion weighting and long echo times. In this work we first provide an example for the type of compartment-specific information that can be obtained with DWS from a small volume of interest in brain white matter. We then propose and discuss a strategy for the analysis of DWS data, which includes the use of models of diffusion in compartments with simple geometries and can be used to extract properties, such as the cytosolic diffusion coefficient of metabolites, which are potential markers for intracellular damage in neurological disorders. We conclude with a brief discussion of the potential role of DWS in the larger scope of tissue microstructural characterization and the complementarity of DWS with less specific but more sensitive microstructural tools, such as diffusion tensor imaging.